Potential Zoonotic Disease Transmission from Macaques to Human in Ecotourism Areas: A Systematic Review - Sepriyoga Virdana1; Rizaldi1*; Rita Maliza1 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Zoonotic diseases pose a significant public health threat, particularly in ecotourism areas where frequent human-macaque interactions increase the risk of pathogen transmission between species. Understanding these dynamics is crucial for safeguarding both human and animal health. This systematic review synthesizes research on the prevalence and transmission of zoonotic pathogens from macaques to humans in ecotourism settings. Methods: The review adhered to PRISMA guidelines, and a comprehensive literature search was conducted across PubMed, Web of Science, Scopus, Google Scholar, and Semantic Scholar to identify relevant publications. Seventeen studies published between 2000 and 2024 were rigorously evaluated. These studies investigated zoonotic disease transmission between macaques and humans in diverse ecotourism settings across eight countries. Results: The analysis revealed that viruses (42%) were the most frequently reported zoonotic pathogens transmitted from macaques to humans, followed by helminths (28%) and protozoa (26%). Transmission occurred through both direct and indirect pathways, including bites, scratches, physical contact, and exposure to contaminated surfaces or objects. Conclusions: The findings underscore the need for robust public health interventions, such as enhanced surveillance, vaccination programs, and hygiene protocols. Effective ecotourism management strategies should also incorporate educational programs for visitors on zoonotic risks, improved hygiene infrastructure, and strict regulations on human-macaque interactions, including maintaining safe distances and prohibiting feeding, to protect both human and animal health.